Commercialization and Mission Drift : Evidence from a Large Chinese Microfinance Institution - Jia, Xiangping; Cull, Robert; Guo, Pei; Ma, Tao (World Bank, Washington, DC, 2016)
Front-line loan officers of microfinance institutions are important in acquiring information on potential borrowers and selecting them in accordance with the microfinance institution's mission. This study uses a unique data set on loan officers and their loan portfolios from China's largest nongovernmental organization microfinance institution to test whether officers' personal characteristics affect the size and quality of their loans. The analysis uses a period in which the institution shifted from reliance on government donations and subsidies to commercial sources of funding. Imposing more commercial incentives on loan officers could affect how they balance potentially competing objectives to serve the poor and pursue profitability. The paper finds that loan officers who were formerly farmers or worked in local government were better able to maintain lending to poorer borrowers, without incurring substantially lower repayment rates on their loans. In short, it appears that the career backgrounds of loan officers did play a role in preventing mission drift.